Assessing Skeletal Muscle Variations in Microvascular Pressure and Unstressed Blood Volume at the Bedside. (October 2014) - De Blasi, Roberto Alberto; Arcioni, Roberto
Abstract Objective Quantitative NIRS measurements for MBV partitioning inside microvessels are of current physiologic and clinical interest. In this study, in healthy subjects, we sought new bedside NIRS variables for noninvasively measuring Vu and Pi changes. Methods Fifteen healthy subjects underwent graded venous congestion for MBV measurements with NIRS and the reference technique strain‐gauge plethysmography. From ΔMBV we calculated vascular compliance, blood flow, and new NIRS variables including Vu and Pit and Pcrit. Results Extrapolating MBV changes to 0 yielded Pit 4.19 ± 0.5 mmHg corresponding to a Vu of 2.53 ± 0.43 mL/100 mL T. The slope for MBV began steeper at values below 18 mmHg (Pcrit). Microvascular compliance measured with NIRS or with strain gauge gave matching results. The change in MBV depended on the oxyhemoglobin increase. No correlation was found between Vu and microvascular compliance or the overall ΔMBV. Cumulative pressure steps showed higher linearity in ΔMBV than that induced by discontinuous steps. Conclusions The new NIRS variables we report could be a practical bench‐to‐bedside tool to assess venous driving pressure for systemic perfusion and measure changes in Vu within the microvascular bed.